Volumetric upper airway assessment in patients with transverse maxillary deficiency after surgically assisted rapid maxillary expansion - Pereira-Filho, V. A. [UNESP]; Monnazzi, M. S.; Gabrielli, Marisa Aparecida Cabrini; Spin-Neto, R. [UNESP]; Watanabe, E. R. [UNESP]; Gimenez, C. M. M. [UNESP]; Santos-Pinto, A. [UNESP]; Gabrielli, Mário Francisco Real [UNESP] (Churchill Livingstone, 2014)
Transverse maxillary deficiency is commonly found in patients with sleep apnea and is also related to abnomial breathing patterns. Maxillary expansion procedures promote widening of the nasal floor and reduce the resistance to airflow, and have a positive influence on nasopharynx function. In order to evaluate volume changes in the upper airway, 15 adult patients with transverse maxillary deficiency underwent surgically assisted rapid maxillary expansion (RME) until a slight overcorrection of the crossbite was obtained. Cone beam computed tomography (CBCT) volumetric images were obtained at three predefined time points. The mean age of the patients was 30.2 (+/- 7.4) years; nine were females and six were males. The area, volume, and the smallest transverse section area of the airway were assessed using Dolphin Imaging 3D software. Statistical comparisons were made of the changes between time periods. No statistically significant differences were found for volume or area. However a significant difference was found between the preoperative and immediate postoperative smallest transverse section area (P < 0.05). Maxillary expansion, as an isolated procedure, does not result in a statistically significant improvement in the airway dimensions and results in an inferior relocation of the smallest transverse section area.
Keywords: maxillary transverse deficiency; oropharynx; malocclusion; airway assessment